Dating the palaeolithic footprints of ‘Le Rozel’ (Normandy, France) - Mercier, Norbert; Martin, Loïc; Kreutzer, Sebastian; Moineau, Virginie; Cliquet, Dominique (Quaternary geochronology, 2019)
Luminescence ages were obtained from six sediment samples at the archaeological site ‘Le Rozel’. These samples are associated with hundreds of footprints left by humans (probably Neanderthals) in the archaeological layers. The single-grain technique was applied to 200-250μm quartz grains, whereas K-feldspar grains were measured using the multi-grain pIRIR225 signal. For quartz, final De estimates were derived in applying a Bayesian model. The comparison of these minerals indicates that the K-feldspar ages are significantly higher than the quartz ages. Nevertheless, the OSL quartz measurements are in agreement with the sedimentological data, and consistent with previous OSL ages obtained in the 2000s for layers in a stratigraphical lower position. It was then concluded that feldspar grains have been likely insufficiently bleached due to the short transportation distance and/or because of a rapid burial by more recent sediments. Such a rapid sedimentation rate would also explain the good preservation of the found numerous human prints. Our new findings indicate that the site was inhabited during the outgoing MIS 5 and the footprints revealed an age of at least 70±10 ka.
Online verfügbar: 23. Dezember 2017, Artikelversion: 28. November 2018
Gesehen am 26.03.2025